Association of endothelin-1 and matrix metallopeptidase-9 with metabolic syndrome in middle-aged and older adults. Issue 1 (December 2015) - Yu, A.; Tam, B.; Yau, W.; Chan, K.; Yu, S.; Chung, T.; Siu, P.
Abstract Background Metabolic syndrome (MetS) contains a cluster of cardiovascular risk factors. People with MetS are more susceptible to cardiovascular disease, diabetes mellitus, and cancer. Endothelin-1 (ET-1) and matrix metallopeptidase-9 (MMP-9) have been implicated in the development of cardiovascular diseases, diabetes mellitus and cancers. This cross-sectional study aimed to examine the association of ET-1 and MMP-9 with MetS in middle-aged and older Hong Kong Chinese adults. Methods 149 adults aged 50 to 92 (n = 75 for non-MetS group and n = 74 for MetS group) were examined. All subjects were screened for MetS according to the diagnostic guideline of the United States National Cholesterol Education Program (NCEP) Expert Panel Adult Treatment Panel (ATP) III criteria. Serum levels of ET-1 and MMP-9 were measured. Independentt test was used to detect differences between non-MetS and MetS groups and between subjects with or without certain metabolic abnormality. The association of the serum concentration of MMP-9 and ET-1 with MetS parameters were examined by Pearson's correlation analysis. Results Serum level of ET-1 is higher in MetS-positive subjects and in subjects with high blood pressure, elevated fasting blood glucose, and central obesity. The serum concentration of MMP-9 is higher in subjects positively diagnosed with MetS and subjects with high blood pressure, elevated fasting blood glucose, low blood high-density lipoprotein-cholesterol (HDL-C), high blood triglycerides, and central obesity. Correlation analyses revealed that serum concentration of ET-1 is positively correlated to systolic blood pressure, waist circumference, fasting blood glucose, and age whereas it is negatively correlated to HDL-C. MMP-9 is positively correlated to systolic blood pressure, waist circumference, fasting blood glucose, and age whereas it is negatively correlated to HDL-C. Conclusion Serum ET-1 is higher in subjects with hypertension, hyperglycemia, central obesity or MetS. Serum MMP-9 is higher in subjects diagnosed with MetS or having either one of the MetS parameters. Both circulating levels of ET-1 and MMP-9 are correlated to systolic blood pressure, waist circumference, fasting blood glucose, HDL-C, and age. Further research is needed to fully dissect the role of ET-1 and MMP-9 in the development of cancers, diabetes and cardiovascular disease in relation to MetS.